Design and Control of an Assistive Device for Elbow Effort-Compensation - Mobedi, Emir; Kim, Wansoo; Leonori, Mattia; Tsagarakis, Nikos G.; Ajoudani, Arash (IEEE/ASME transactions on mechatronics, 2023)
In this article, we introduce an assistive device for the elbow joint that is easily wearable, lightweight, and cable driven using a series elastic actuation principle implemented by an endless-shape elastic bungee element. This type of elastic element is selected due to its intrinsic damping, and compliant features similar to human muscles, which provide mechanical filtering against dynamic uncertainties such as impulsive forces, and oscillated movements because of possible controller issues. Furthermore, a spool system is designed targeting to maximize the transmission of the generated elastic force to the wearer while avoiding multiple coiling for the cable wrap/release operation. The design parameters of the device are selected through design and optimization studies. The manufactured actuator's performance is validated on a rigid link under position and force control modes. To demonstrate the effectiveness of the elastic element, we conducted actuator validation tests with and without bungee cases. The results show that while the bungee-integrated setup can transfer the generated elastic force to the link without oscillation at different frequency movements (0.05-0.16 Hz), the bungee-excluded setup performs unstable movements under the same control gains, producing 50.74% more vibrations detected through fast Fourier transform analysis. In addition, to test the system under aggressive conditions, we applied impacts to it, and the results indicate that the damping ratio index of the bungee incorporated system is 56.14% more than that of without bungee case, demonstrating the intrinsic safe behavior of the mechanism. Finally, the device is assessed on six human subjects (different arm weights and dimensions) in a simulated industrial painting task with 5 min duration, with an average 22.3^\circ /\text{s} elbow velocity under force control. The average effort reduction on biceps muscle among the subjects is measured 64.42% with respect to the without assistance test.